SHOX in short stature syndromes - Blaschke, Rüdiger Jörg; Rappold, Gudrun (Hormone research, 2001)
Linear growth is a multifactorial trait that is influenced and regulated by a combination of environmental and internal factors. Among the intrinsic determinants of final body height, genetic factors have become more and more prominent, and the list of genes involved in growth-related processes has been extended accordingly. One of the most exciting additions to this list is represented by the discovery of the pseudoautosomal gene SHOX. Originally described as a gene responsible for idiopathic short stature, it has become clear that SHOX mutations can also cause mesomelic short stature and Madelung deformity in Léri-Weill syndrome. In addition, recent studies implicate SHOX haploinsufficiency in a variety of somatic Turner syndrome stigmata.
Elektronische Reproduktion der Druck-Ausgabe
Published online: November 17, 2004
Gesehen am 24.03.2021